EFEKTIFITAS PENGUKURAN LINGKAR BETIS SEBAGAI PREDIKTOR BAYI BERAT LAHIR RENDAH DIKABUPATEN SAMBAS TAHUN 2015 - Nurlian, Yayan; Hernawan, Andri Dwi; Marlenywati, Marlenywati (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
LBW rate West Kalimantan in 2013 is much higher at 14.8% than the national rate is 10.2% of LBW. Besides the rate of weighing babies when birth has reached 70% and many people are childbirth at home around 66.6%. LBW rate Sambas district in 2014 is 411 babies and case amount chilbirth is helped by traditional healer and non-health profesional is 857 babies than childbirth total around 11.523 babies. The calibrated-scales and unskilled midwives make a risk of LBW. LBW have a significant impact on the nutritional status of infants and will affect the development phase and furthermore babies growth. The research aims to get gain sensitivity and specificity calf circumference measurement as a low birth weight babies in Sambas district in 2015.This study used a cross-sectional design. 268 babies predictor samples are determined by using total sampling. The test used is an epidemiological screening (sensitivity and specificity) and Pearson correlation.The results showed that the calf circumference measurement has a high sensitivity 93%, specificity of 88.28%, and the value of Pearson correlation 0.667 (66.7%).Potential of calf circumference in predicting LBW case is very good, and therefore required new innovation to the specific measurement tool that fits calf circumference cut of point making it easier for health professionals in the measurement when the scale does not exist.Keywords : Low birth weight, Calf circumference, Sensitivity, Specificity